PENGARUH PENGGUNAAN CHATGPT TERHADAP HASIL BELAJAR PADA MATA PELAJARAN EKONOMI SISWA KELAS XI SMA N 12 KOTA JAMBI - Cindy Elmalia; Rosmiati; Hidayatul Arief (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The results of students' learning in Economics still show suboptimal performance, as evidenced by the fact that many students have not yet reached the minimum passing score. This is partly due to the limited use of technology in the learning process, resulting in monotonous and less interactive learning activities. This study aims to investigate the impact of using artificial intelligence (AI) ChatGPT on students' learning outcomes.The study used an experimental method with a post-test only control group design. The research subjects consisted of two classes, an experimental class (XI F1) and a control class (XI F7). The research instrument was a multiple-choice test that had undergone validity and reliability testing. Data analysis was performed through normality testing, homogeneity testing, and hypothesis testing using Independent Samples t-test. The results of the study showed that the mean score for the experimental class was 84.0540, which was higher than the mean score for the control class, which was 78.7794. The hypothesis test results showed a significance value of 0.019 (<0.05), indicating a significant difference between the two classes. Therefore, the use of AI ChatGPT has a significant impact on students' learning outcomes.